Corrigendum to: Evaluation of a quality improvement intervention to reduce anastomotic leak following right colectomy (EAGLE): pragmatic, batched stepped-wedge, cluster-randomized trial in 64 countries: corrigendum - Avellaneda, Nicholas; Fütterer, Carsten Dietmar; Reißfelder, Christoph; Şandra-Petrescu, Flavius Ionuţ; Herrle, Florian; Hardt, Julia; Lamm, Lena; Seyfried, Steffen (The British journal of surgery, 2024)
This is a corrigendum to: ESCP EAGLE Safe Anastomosis Collaborative and NIHR Global Health Research Unit in Surgery, Evaluation of a quality improvement intervention to reduce anastomotic leak following right colectomy (EAGLE): pragmatic, batched stepped-wedge, cluster-randomized trial in 64 countries, British Journal of Surgery, Volume 111, Issue 1, January 2024, znad370, https://doi.org/10.1093/bjs/znad370The originally published version of this manuscript has been amended to make the following corrections to the section entitled “Collaborators”.
Gesehen am 30.09.2024
Collaborators (country in alphabetical order, and hospital): Germany: A. Hoetzel, A. Jud, D. Jauch, F-F. Stefan, H. Neeff, P. Holzner, P. Nguyen (University Hospital Freiburg), A. Ryl, F. Kehl, F. Pullig, J. Baral, S. Münch (Klinikum Karlsruhe), C. Fütterer, C. Reißfelder, F. Sandra-Petrescu, F. Herrle, J. Hardt, L. Lamm, S. Seyfried (Mannheim University Medical Center (Universitätsmedizin Mannheim)), A. Gharbi, F. Aydin, G. Stavrou, J. Sperber, J. de Deken, K. Schwarzkopf, R. Widyaningsih (Klinikum Saarbruecken)